User experience framework for understanding user experience in blockchain services. Issue 158 (February 2022) - Jang, Hyeji; Han, Sung H.
Highlights: The importance of user experience (UX) in blockchain services has increased. However, systematic UX research for blockchain is disregarded. A framework for understanding the nature of UX in blockchain services is proposed. Proposed framework helps to effectively define UX in blockchain services. The efficacy of the proposed framework is validated by the results of a case study. Abstract: Since the advent of blockchain, interest in the technology has rapidly increased, bringing the launch of new blockchain services. User experience (UX) research provides a basis for systematically understanding and improving the experience of users, and must be carried out regardless of service type. However, it seems that research on the UX of blockchain services has not kept up with the speed with which blockchain technology has been implemented. To remedy this situation, this study proposes a UX framework for understanding the nature of UX in blockchain services. An extensive literature survey related to UX, blockchain technology, and blockchain services was conducted to define UX in blockchain services and identify the elements of UX. Blockchain functions and values that had been newly introduced in blockchain services were identified to help clarify the nature of UX in blockchain services. The proposed framework consists of two parts: a general UX and a technological UX. The elements and sub-elements of the defined UX are derived with detailed explanations. The proposed framework was applied to four blockchain services as a case study. The appropriateness and applicability of the framework are supported by the results of this case study. This study is expected to inspire researchers to provide enhanced UX in blockchain services in the future.